Childhood maltreatment, revictimization, and stay-leave decision-making. Issue 2 (3rd May 2021) - Selvey, Alicia; Barry, Amanda; Budde, Emily; Allbaugh, Lucy J.; Kaslow, Nadine J.
Abstract: Survivors of childhood maltreatment (CM) are at increased risk of revictimization, including intimate partner violence (IPV). While research has established some mediators of this link, less is known about the process of stay-leave decision-making among CM survivors in abusive partnerships and how these decision-making processes may inform the CM-IPV link. Certain populations of revictimized women are understudied, such as low-income African American women, despite the fact that they experience higher rates of CM and IPV than their White counterparts. The present study is an investigation of stay-leave decision-making among a low-income sample of 121 African American women with recent IPV exposure. Severity of CM, by both type of maltreatment and cumulative maltreatment, was examined as related to salience of distinct stay-leave decision-making factors. Stay-leave decision-making factors were then tested as mediators of the relation between CM and severity of IPV. Using multivariate analyses of variance (MANOVA), experience of physical neglect was found to be especially associated with more consideration of poor social support, while other specific forms of CM were not differently associated with individual stay-leave decision-making factors. Using bootstrapping analyses, associations were found between greater severity of CM and three specific stay-leave factors: concerns related to social embarrassment, poor social support, and financial problems. Further, social embarrassment emerged as the most salient mediator of the relations between CM and three forms of IPV (i.e., physical abuse, nonphysical abuse, and controlling behaviors). The implications of these findings for clinical intervention and future research for this high-risk population are discussed.